Characterization of green fluorescent proteins by 193 nm ultraviolet photodissociation mass spectrometry. Issue 10 (10th April 2014) - Cannon, Joe R.; Kluwe, Christien; Ellington, Andrew; Brodbelt, Jennifer S.
<x xml:space="preserve">Abstract</x> We investigate the utility of 193 nm ultraviolet photodissociation (UVPD) in comparison to CID, higher energy CID (HCD), and electron transfer dissociation (ETD) for top down fragmentation of highly homologous green fluorescent proteins (GFP) in the gas phase. Several GFP variants were constructed via mutation of surface residues to charged moieties, demonstrating different pIs and presenting a challenge for identification by mass spectrometry. Presented is a comparison of fragmentation techniques utilized for top down characterization of four variants with varying levels of surface charge. UVPD consistently resulted in identification of more fragment ions relative to other MS/MS methods, allowing higher confidence identification. In addition to the high number of fragment ions, the sites of fragmentation were more evenly spread throughout the protein backbone, which proved key for localizing the point mutations.